An Alternative Perspective On Demand And Supply To Forecast Inflation In The Philippines Using State Space Modeling - Manuel, Sarah Mae A.; Associate Professor Peter Julian Cayton, PhD.
ABSTRACT

The Philippine economy perennially faces the problems of high inflation, potentially driven by imbalances in demand and supply. Using state space models, this paper proposes a novel methodology that primarily hinges on analyzing structural disturbances between the demand and supply gap. It adopts the outline provided by Sharma and Padhi (2021) in producing demand and supply mismatch indices (DSMI) as important driver of inflation. While the decomposition of real output, effectively capturing information on the interdependencies of industries, particularly the upstream and downstream flows of goods and services within the economy. Our two main findings include: (i) There is a larger component of the demand side compared with the supply side in the GDP cyclical component, as revealed through the IOT linkages and the state space model, and (ii) the demand and supply mismatch index series also align with the direction of headline inflation. Other models, such as the univariate ARIMA, ETS, and ARDL and ARIMAX with output gap, as well as the demand and supply components are used. Among these, the ARDL model applied to the DSMI provided the closest out-of-sample estimates to the actual values of headline inflation.
Includes Tables and Charts.
Keywords: Inflation Forecasting -- Input-Output Framework -- Supply and Demand Shocks -- State Space Model